2020
DOI: 10.1002/mabi.202000197
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Piezoelectric PVDF‐TrFE Fibrous Scaffold to Guide Cell Adhesion, Proliferation, and Alignment

Abstract: Severe peripheral nervous system injuries currently hold limited therapeutic solutions. Existing clinical techniques such as autografts, allografts, and newer nerve guidance conduits have shown variable outcomes in functional recovery, adverse immune responses, and in some cases low or minimal availability. This can be attributed in part to the lack of chemical, physical, and electrical cues directing both nerve guidance and regeneration. To address this pressing clinical issue, electrospun nanofibers and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 82 publications
2
40
0
Order By: Relevance
“…39 Furthermore, SES fibers result in values around 85% P(VDF-co-TrFE) (75/25) depending on the fiber orientation 6 and 88% ⊎-phase using P(VDF-co-TrFE) (70/30). 43 Those findings together with the results of the MEW-processed fibers in this study indicate the high impact of the TrFE content, as well as the applied electric field, which is in general higher for SES and/or the fabrication process (melt-or solvent-based), on the resulting ⊎-phase fractions and the overall crystallinity.…”
Section: Xrd Measurements Crystallinity and ⊎-Phase Contentsupporting
confidence: 67%
“…39 Furthermore, SES fibers result in values around 85% P(VDF-co-TrFE) (75/25) depending on the fiber orientation 6 and 88% ⊎-phase using P(VDF-co-TrFE) (70/30). 43 Those findings together with the results of the MEW-processed fibers in this study indicate the high impact of the TrFE content, as well as the applied electric field, which is in general higher for SES and/or the fabrication process (melt-or solvent-based), on the resulting ⊎-phase fractions and the overall crystallinity.…”
Section: Xrd Measurements Crystallinity and ⊎-Phase Contentsupporting
confidence: 67%
“…Electrospun PVDF scaffolds also suggested as a powerful mean with the ability to direct neural stem cells differentiation into neuronal and glial cells [73]. Another study of the application of Electrospun PVDF in PNS regeneration offered electrospun nanofibers composed of piezoelectric polyvinylidene flouride-triflouroethylene (PVDF-TrFE) that promote the adhesion and alignment of Schwann cells and fibroblasts [74].…”
Section: Electrical Conductivity and Stimulationmentioning
confidence: 99%
“…The results showed that the contact angle decreased when Nar is added ( p < 0.05). The small contact angle indicates that the hydrophilicity of the PCL/PEG-Nar nanofiber membrane was significantly improved and favorable for cell adhesion and growth ( Martins et al, 2018 ; Orkwis et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%